Shiksha: Bharatiya Paripekshya - BHARDWAJ, B.P.; SINGH, PARUL (INDIAN EDUCATIONAL REVIEW, 2025)
he chapters are well organised from historical perspective, definition of Shiksha, philosophical foundation, social contexts, linguistic framework, health and education (Ayurveda) curriculum and pedagogy, Acharya (A model teacher) and their training, arts and sciences, assessments, Indian research methodology, goal of education, educational models of Rabindra Nath Tagore, Sri Aurobindo and Mahatma Gandhi. In short it is an encyclopedic reference book on Bharatiya Education. This will surely be a useful guide to all those who want to understand and implement NEP 2020. At its core, this book is an inquiry into the history of the process of learning in Bharat. The work opens by revisiting the words of Maharishi Kan.āda: “Yato abhyudayanih. śreyasasiddhih. sa dharmah.” (The means through which both Abhyudaya (material prosperity) and nihśreyasa . (spiritual welfare), are attained is called Dharma.) This aphorism encapsulates the dual objective of education in ancient Bharat: The Pursuit of both worldly progress and spiritual enlightenment. The author tries to connect ancient wisdom with modern imperatives, most notably the need to counter the dependency on Western paradigms. The book situates itself as both a scholarly investigation and a call for a shift in the educational paradigm. Further, it connects the goal of NEP 2020 with potential practices drawn from the accumulated knowledge of experience. One of the book’s significant strengths is its rigorous engagement with primary sources. The book starts from the Vedic sources such as RigVeda, Upanishads and other later texts and concludes with the various models propounded by Swami Vivekananda, Sri Aurobindo, Rabindra Nath Tagore and Mahatma Gandhi. The book has plenty of references from every field of knowledge. One such example of pedagogy is from Mundaka Upanishad, where the sage Shaunak inquires Rishi Angira about the means to know everything, a dialogue that defines knowledge into Para Vidya (knowledge of the ultimate reality) and Apara Vidya (knowledge leading to worldly benefits). It underscores the central thesis of Shiksha that true education must transcend academic instruction to embrace the cultivation of inner wisdom